Taking ownership : the relationship between self-representation and writing development in a science extended curriculum programme at the Cape Peninsula University of Technology - Reiners, Ayesha (School of Education, 2016)
This study challenges the prevalence of the literacy deficit views of student writing at Cape Peninsula University of Technology where I teach. The study is located in an Extended Curriculum Programme in the Applied Sciences and stretches across the Analytical Chemistry and Horticulture disciplines. It argues that writing is an act of identity and thus it is imperative to engage with the nuances of identity in text. I focus on the notion of the self and how this is represented in student writing. Students often view writing as difficult because they do not identify with the 'me' in their writing as dominant university discourses and practices often overpower them. The theoretical resources drawn on are situated in the academic literacies field which emphasizes the contested nature of academic meaning making practices (Lea and Street 1998, Lillis and Scott 2007). In particular, I use Clark and Ivanic's 'clover-leaf model (1997) that identifies three aspects to research writer identity in a text: the autobiographical self which writers bring with them to the act of writing. This is shaped by their life histories and the social group with which they identify; the discoursal self, which is how writers represent themselves in the text, based on the discourse choices they make as they write, and the authorial self, which is how writers assert themselves in their writing. In addition, the three aspects above are all affected by the socio-culturally available subject-positions and patterns of privileging among them that exist in the sociocultural context. My research extends Ivanic's research on the contested nature of writing by shifting the focus from academic writing of mature students in higher education, to explore academic and journal writing of first year students in an extended programme at a University of Technology in South Africa in a time of rapid transition. In order to explore these aspects of identity in student text in the Applied Sciences, I ask how students represent themselves in a text and whether there are any shifts or changes within an academic year. I also ask what these self-representations mean for teaching in an extended curriculum programme. Includes bibliographical references (pages 74-78).